Influencia de la sustitución de ingredientes en las características reológicas, calóricas y sensoriales en un cake tipo magdalena - Coello, N. (2010)
The present study examines the effect on the rheological, sensorial and caloric properties in a bakery product: the madeleine, when is substituted wheat flour and sugar for resistant starch and Rebaudioside-A, respectively. The experimental tests allowed the study and analysis of the effect of substitutions on the physical properties of the madeleine, emphasizing on the viscosity of the initial dough and volume of the final product. In these tests with different substitutions was also considered the sensorial properties evaluating the taste, and texture and water activity as part of product stability during storage. Was substituted 30% of wheat flour by resistant starch, which provides an excellent source of functional fiber to the final product. The replacement of 50% of sugar by Rebaudioside-A, a natural sweetener, reduces the calories, achieving a healthy product.